Identificación, aislamiento y caracterización del virus de artritis y enecefalitis caprina den la provincia de Salta - Dodero, Ana Mariela (2023)
Small Ruminant Lentiviruses (SRLV) are present worldwide and recently described in Buenos \nAires province in 2017, however extension and infection importance in the Salta province is \nunknown. This virus infection can present four classic clinical forms: articular, mammary, \npulmonary and nervous. This disease causes numerous production losses such as those \nresulting from reduced feed intake due to the pain of the arthritic pathology; the drop in milk \nproduction, which is also justified by mastitis that leads to early drying of the animal and loss \nof the mammary means; deaths caused by encephalitis and pulmonary diseases added to the \nimpact of premature discards induced by the virus. The aim of the study was to identify, isolate \nand molecularly characterize the SRLVs present in the Salta province in order to detect the \ncirculating strains and develop diagnostic methods to be applied in control programs. About \n927 adult animals were sampled from 32 herds distributed in three ecoregions, Chaco Salteño \n(CS), Valles y Quebradas áridas (VA) and Valles Templados (VT), together with a socio-economic and productive survey at each site. One of the farms was used as an experimental \nherd for biological sampling, practice of management measures and clinical follow-up of a \ncontrol case. Herds were screened with commercial indirect ELISAs and concordance tests \nwere performed. The overall seroprevalence was 8.26% and by ecoregion: 9.17% in CS, \n6.48% in VA and 11.35% in VT. Genomics sequences were obtained from the gag region, \nwhich allowed the molecular characterization of the strains as a B1 subtype, the development \nof specific diagnostic PCRs, and the expression and purification of the viral recombinant \nprotein p25, followed by the first steps in the evaluation of its potential use in an indirect ELISA. \nPrimary sheep and goat cultures were produced, characterised and challenged with viral \ninocula obtaining clear cytopathic effects, but unsuccessful in isolating infective strains. Based \non the survey data, risk factor analyses for the presence of the infection were carried out, being \nmore risky if the herd is not dewormed, mechanically milked or collectively bred. Finally, a \nmanagement protocol was proposed for the control of SRLVs based on the early identification \nof infected animals and the selection of uninfected animals for restocking.\nThe results reflect the presence of SRLVs in the Salta province, probably derived from animal \nimportations; the importance of livestock activity in the area studied; and the need to develop specific surveillance plans for SRLV control, thus avoiding the spread of the infection.